The Warriors - Walter Hill; Tyler, Brian; David Harris; Dorsey Wright; James Remar; Marcelino Sánchez; Tom McKitterick; Michael Beck (USA Paramount Pictures, 1979)
The Warriors are mistakenly accused of killing a big time gang leader named Cyrus. Soon they have every gang in the city out to get revenge. The Warriors must make their way from one end of New York to their turf on the other side of the city.
A gang called The Warriors are framed for killing a gang leader trying to unite all the gangs in the area. With other gangs gunning for them they must get back to the home turf of Coney Island... Alive.
Sol Yurick
Languages : English, German Subtitles : English, Turkish, Arabic, Bulgarian, Czech, Icelandic, Polish, Dutch, Romanian
Keywords: Crime; Drama; Thriller; Action